PENERAPAN MEDIA PEMBELAJARAN LUMIO BY SMART PADA PEMBELAJARAN FIKIH BAB QURBAN KELAS IX MTs - Maulida, Ameylia; Hakim, Rosyida; Mardhiyah, Ainatul; Sutiah (Rabbani: Jurnal Pendidikan Agama Islam, 2025)
Today's learning offers a variety of options. Education and learning are no longer confined to classrooms but can take place anywhere. Technological advancements have driven innovation in education, particularly in the use of learning media. This study is motivated by the need for variety in existing learning media. The research aims to examine the effectiveness of using the digital learning media Lumio by Smart in improving students' learning outcomes on the topic of Fiqh Qurban in grade IX MTs. Using a mixed-method approach, this study involved 11 students, utilizing pre-test and post-test methods as the primary tools, supported by observation and documentation. The results indicate a significant improvement, with the average score increasing from 49 in the pre-test to 80 in the post-test, representing an average gain of 31. The use of Lumio by Smart, equipped with interactive features such as quizzes, educational games, and animations, made the learning process more engaging, interactive, and enjoyable. Overall, this study concludes that Lumio by Smart is an effective learning media to enhance student learning outcomes, particularly on the topic of Fiqh Qurban. The study recommends further development of the platform’s design to increase its appeal.